Gene expression atlas for the food security crop cassava. Issue 4 (24th January 2017) - Wilson, Mark C.; Mutka, Andrew M.; Hummel, Aaron W.; Berry, Jeffrey; Chauhan, Raj Deepika; Vijayaraghavan, Anupama; Taylor, Nigel J.; Voytas, Daniel F.; Chitwood, Daniel H.; Bart, Rebecca S.
Summary: Cassava ( Manihot esculenta ) feeds c . 800 million people world‐wide. Although this crop displays high productivity under drought and poor soil conditions, it is susceptible to disease, postharvest deterioration and the roots contain low nutritional content. Here, we provide molecular identities for 11 cassava tissue/organ types through RNA‐sequencing and develop an open access, web‐based interface for further interrogation of the data. Through this dataset, we consider the physiology of cassava. Specifically, we focus on identification of the transcriptional signatures that define the massive, underground storage roots used as a food source and the favored target tissue for transgene integration and genome editing, friable embryogenic callus (FEC). Further, we identify promoters able to drive strong expression in multiple tissue/organs. The information gained from this study is of value for both conventional and biotechnological improvement programs.